Autobiography through the Exile Paradigm: The Olaudah Equiano Story (2004)
This paper examines the relevance of biographical works in literary studies. Using Oluadah Equiano’s story, the essay treats thematic issues with regard to the slave trade and its consequences on Africans. It posits that what led to the success of the story as a historical document is its effectiveness as a tool in the anti-slavery campaign